Developing Leadership Pipelines in Maine School Districts: Lessons Learned from a School-University Partnership - Mette, Ian; Webb, Betsy (Maine Policy Review, 2018)
The authors describe the Bangor Educational Leadership Academy, a partnership between the Bangor School Department and the University of Maine Educational Leadership Program, which enables researchers and practitioners to work more collaboratively to bridge the theory-practice gap that often plagues schools.
Keywords: educational leadership; Maine; Bangor; University of Maine